Effects of methylprednisolone combined with advanced antibiotics and antiviral drugs on serum immunoglobulin and inflammatory factor levels in patients with viral pneumonia: Factors in patients with viral pneumonia - Yue, Lixia; Yan, Yihe (Cellular and Molecular Biology, 2023)
Viral pneumonia (VP) is known for its wide transmission and severe pathological damage. ninety cases of VP patients were rolled into an experimental group (group E, methylprednisolone + advanced antibiotics + antiviral drugs) and a control group (group C, methylprednisolone), with 45 cases in each group. General information about the patients, inflammatory factors, serum immunoglobulins, T lymphocyte subsets, and treatment outcomes (efficiency rate, conversion rate to negative) were compared. In group E, interleukin-6 (IL-6) (0.18±0.07) ng/L was inferior to in group C (0.33±0.09) ng/L, p<0.05; tumor necrosis factor-alpha (TNF-α) (17.22±4.13) ng/L was inferior to group C (26.07±4.08) ng/L, p<0.05; lgA (0.81±0.22) g/L was superior to in group C (0.68±0.17) g/L, P<0.05; lgM (1.62±0.13) g/L was superior to group C (1.09±0.03) g/L, p<0.05; lgE (0.19±0.02) g/L was inferior to group C (0.23±0.03) g/L, p<0.05; CD4+/CD8+ ratio (1.71±0.33) was superior to group C (1.24±0.43), p<0.05; the total efficiency rate in group C (77.78%) was inferior to group E (97.78%), p<0.05; the conversion rate to negative of viral antigens in group E (91.11%) was superior to in group C (64.44%), p<0.05. methylprednisolone in combination with advanced antibiotics and antiviral drugs is an effective treatment approach for VP.